MANAGEMENT CONSULTING, CRITICAL ANALYSIS AND THE LATEST VIEW ON THE DEFINITION - Voloshyn, Ye. O. (The actual problems of regional economy development, 2024)
This article examines the issue of defining management consulting. The goal was a comprehensive review of definitions by various scientists, common features between definitions, differences, critical analysis of scientific approaches to this definition, formation of the author's interpretation of management consulting based on the analysis of the history of the consulting services market. The research used general scientific methods of grouping, generalization, comparison, analysis and synthesis, et. Based on the analysis of existing definitions, the author offers his own definition, which is broad enough to cover the entire range of management consulting activities, and at the same time specific enough to be clear and practical, which will contribute to the development of the theoretical basis of management consulting and the elimination of terminological gaps. The role of management consulting in the modern world is analyzed and it is argued that it is an important tool for increasing the efficiency of enterprises, organizations, allows them to get an independent assessment of their activities, develop and implement effective solutions to solve management problems. Management consulting (consulting) - provision of independent, objective and qualified services for solving management problems to improve business efficiency, covers a wide range of activities, from strategic planning to the implementation of new business processes and technological solutions, can be provided in any business, regardless of its size, industry or stage of development. The author emphasizes the main characteristics of management consulting, such as independence (consultants must be independent from the organization to which they provide services), objectivity (consultants must be objective in their assessments and recommendations), professionalism (consultants must have the necessary knowledge and experience to provide quality services). A creative view of management consulting as a compass that helps enterprises and organizations find the correct path to success is also offered.